(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article provides information aimed at covering the buildings of ministries and state organizations with solar panels using energy-saving and renewable energy sources and reducing energy consumption in these organizations and it is recommended to use ongrid photoelectric systems to reduce energy consumption.